Chemical, mechanical and sensory monitoring of hot air- and infrared-roasted hazelnuts (Corylus avellana L.) during nine months of storage. (15th February 2017) - Belviso, Simona; Dal Bello, Barbara; Giacosa, Simone; Bertolino, Marta; Ghirardello, Daniela; Giordano, Manuela; Rolle, Luca; Gerbi, Vincenzo; Zeppa, Giuseppe
Highlights: Two hazelnut cultivars were roasted with hot air and infrared systems and monitored during storage. The major oxidative stability was reached when hazelnuts were roasted with hot air at 120 °C/40 min. High antioxidant activity was maintained during storage (6 months at 4 °C). Use of hot air seemed to cause a higher decrease in the rupture force of hazelnuts. Hazelnuts roasted with the two systems at 170 °C had significantly different sensory features. Abstract: Roasted hazelnuts can be consumed as whole nuts, or as an ingredient in the confectionary and bakery industries and are highly appreciated for their typical taste, aroma and crunchy texture. In this work, two hazelnut types (TGT, Ordu) from two harvests were roasted using two different systems (hot air, infrared) at different time/temperature combinations, and the evolution of oxidative stability, the total phenolic content (TPC), the antioxidant capacity, the mechanical and acoustic properties and the sensory perception were determined during storage. The results showed that the oxidative stability was increased by roasting hazelnuts at 120 °C for 40 min with hot air system. Similar overall trends were not found for the TPC, the antioxidant capacity and the mechanical-acoustic properties. However, for the maintenance of high antioxidant activity, a storage time of 6 months at 4 °C is recommended. The two roasting systems gave hazelnuts with significant sensory differences only at high roasting temperature.